겨울철 한국 대학생의 열적 반응 - 배귀남; 김명호; 김영일 (한국실내환경학회, 2007)
Experiment on the thermal response of college-age Korean was conducted in a thermal environmental chamber during winter season. Eight environmental conditions composed of five air temperatures (18～26℃) and two relative humidities (40, 60%) were selected. To investigate the uniformity of thermal environments, the spatial distributions and the temporal variations of thermal parameters were examined in the test chamber. Subjects of 7 females or 7 males were questioned in the chamber for three hours, where thermal and comfort sensations were surveyed every fifteen minutes. The repeatability and temporal variation of thermal response were discussed. The thermal sensation votes of subjects were compared with the predicted mean votes calculated from the thermal parameters and human parameters. The correlation between thermal sensation votes and comfort sensation votes of subjects were discussed.